(untitled) (SAARC Journal of Agriculture, 2019)
Agriculture is the primary occupation for the majority of Nepalese populace for their livelihood; the case is especially true for rural areas of Nepal. While both male and female engage in diverse agricultural activities, gender-specific roles in agricultural decision-making are significant. A survey study was conducted in three wards of Kanchanpur district (Majhgau-14, Bhuda-02, and Baghphata-19) to examine the gender-specific labor input in vegetable production activities. Eighty households were chosen by random sampling and a scheduled interview was carried out. Most of the activities such as fence construction, transplanting, fertilizer use, harvesting, cleaning, and grading were found typically female’s responsibility. However, males were found dominantly involved in land preparation. Also, males were found to have relatively more access to, and control over farm resources and played dominant role in decision making than women. The findings of this study revealed that there are gender-specific domains in rural farming system. Therefore, there is a need to develop gender friendly technology and policy while formulating specific project planning and development efforts. SAARC J. Agri., 16(2): 109-118 (2018)